A marriage made at Woodstock - Pelletier, Cathie (New York : Crown Publishers, 1994)
Fred and Lorraine are a fortysomething couple who have evolved and grown in seperate directions, hoping that their marriage can survive the nineties.
A novel.
Library Journal
Publisher's Weekly
New York Times
Maine author.
Keywords: Marriage -- Maine -- Portland -- Fiction; Maine -- Fiction; Portland (Me.) -- Fiction; Domestic fiction